Odpowiedzi

2010-03-05T20:00:54+01:00
Wszystkie przykłady w każdym zadaniu robi się identycznie więc będę dokładnie rozpisywał tylko pierwszy.
1.
a) 12²=(10+2)²=(10+2)*(10+2)=10²+40+2²=100+40+4=144
b) 21²=(20+1)*(20+1)=20²+40+1²=441
c) 19²=(20-1)*(20-1)=20²-40+1²=361
d) 18²=(20-2)*(20-2)=20²-80+2²=324
e) 32²=(30+2)*(30+2)=30²+120+2²=1024
f) 98²=(100-2)*(100-2)=100²-400+2²=9604
g)101²=(100+1)*(100+1)=100²+200+1²=10201
h)49²=(50-1)*(50-1)=50²-100+1²=2401

2.
a)101*99=(100+1)*(100-1)=100²-1²=10000-1=9999
b)28*32=30²-2²=896
c)47*53=50²-3²=2481
d)71*69=70²-1²=4899
e)198*202=200²-2²=39996
f)504*496=500²-4²=249984
g)1003*997=1000²-3²=999991
h)580*620=600²-20²=359600

3.
a) (x+9)²=(x+9)*(x+9)=x²+18x+9²=x²+18x+81
b) (8+y)²=64+16y+y²
c) (2a+3)²=4a²+12a+9
d) (4x+5y)²=16x²+40xy+25y²
e) (√2+b)²=2+2√2b+b²
f) (3a+√3)=9a²+6√3a+3

4.
a) (5-b)²-(5-b)*(5-b)=5²-10b+b²=25-10b+b²
b) (a-4)²=a²-8a+16
c) (3a-2b)²=9a²-12ab+4b²
d) (7x-1)²=49x²-14x+1
e) (2√2-5x)²=8-20√2x+25x²
f) (√2x-√8y)²=2x²-8xy+8y²
2010-03-05T21:31:32+01:00
Zad.1
wzór (a+b)²=a²+2ab+b²
lub (a-b)²=a²-2ab+b²
a) 12²=(10+2)²=10²+4*10+2²=100+40+4=144
b) 21²=(20+1)²=20²+40+1²=400+40+1=441
c) 19²=(20-1)²=20²-40+1²=400-40+1=361
d) 18²=(20-2)²=20²-80+2²=400-80+4=324
e) 32²=(30+2)²=30²+120+2²=900+120+4=1024
f) 98²=(100-2)²=100²-400+2²=10000-400+4=9604
g) 101²=(100+1)²=100²+200+1²=10000+200+1=10201
h) 49²=(50-1)²=50²-100+1²=2500-100+1=2401

Zad.2
wzór (a+b)(a-b)=a²-b²
a) 101*99=(100+1)(100-1)=100²-1²=10000-1=9999
b) 28*32=(30-2)(30+2)=30²-2²=900-4=896
c) 47*53=(50-3)(50+3)=50²-3²=2500-9=2481
d) 71*69=(70+1)(70-1)=70²-1²=4900-1=4899
e) 198*202=(200-2)(200+2)=200²-2²=40000-4=39996
f) 504*496=(500+4)(500-4)=500²-4²=250000-16=249984
g) 1003*997=(1000+3)(1000-3)=1000²-3²=1000000-9=999991
h) 580*620=(600-20)(600+20)=600²-20²=360000-400=359600

Zad.3
wzór (a+b)²=a²+2ab+b²
a) (x+9)²=x²+18x+9²=x²+18x+81
b) (8+y)²=8²+16y+y²64+16y+y²
c) (2a+3)²=(2a)²+12a+3²=4a²+12a+9
d) (4x+5y)²=(4x)²+40xy+(5y)²=16x²+40xy+25y²
e) (√2+b)²=(√2)²+2b√2+(b)²=2+2√2+b²
f) (3a+√3)²=(3a)²+6a√3+(√3)²=9a²+6a√3+3

Zad.4
wzór (a-b)²=a²-2ab+b²
a) (5-b)²=5²-10b+b²=25-10b+b²
b) (a-4)²=(a)²-8a+(4)²=a²-8a+16
c) (3a-2b)²=(3a)²-12ab+(2b)²=9a²-12ab+4b²
d) (7x-1)²=(7x)²-14x+1²=49x²-14x+1
e) (2√2-5x)²=(2√2)²-20x√2+(5x)²=8-20x√2+25x²
f) (√2x-√8y)²=(√2x)²-2*√2*√8xy+(√8y)²=2x²-8xy+8y²